2012
DOI: 10.1073/pnas.1202593109
|View full text |Cite
|
Sign up to set email alerts
|

LeishmaniaTDR1 structure, a unique trimeric glutathione transferase capable of deglutathionylation and antimonial prodrug activation

Abstract: Thiol-dependent reductase I (TDR1), an enzyme found in parasitic Leishmania species and Trypanosoma cruzi, is implicated in deglutathionylation and activation of antimonial prodrugs used to treat leishmaniasis. The 2.3 Å resolution structure of TDR1 reveals a unique trimer of subunits each containing two glutathione-S-transferase (GST) domains. The similarities of individual domains and comparisons with GST classes suggest that TDR1 evolved by gene duplication, diversification, and gene fusion; a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
(46 reference statements)
0
25
0
1
Order By: Relevance
“…Polyamine biosynthetic pathway provides spermidine for trypanothione biosynthesis, via conjugation with glutathione to produce glutathionyl-spermidine and trypanothione, the main anti-oxidant of the parasites against host cell oxidative burst [67], although recently, the importance of glutathione as a substantial player in the overall redox power of the parasite has been proposed [68]. Interestingly, variation in total level and the reduced: oxidized ratio of trypanothione is a typical response in antimonial treatment [69], also detected in a CE metabolomic study [56], which is in tune with partial crossresistance between these two drugs [61].…”
Section: Resultsmentioning
confidence: 99%
“…Polyamine biosynthetic pathway provides spermidine for trypanothione biosynthesis, via conjugation with glutathione to produce glutathionyl-spermidine and trypanothione, the main anti-oxidant of the parasites against host cell oxidative burst [67], although recently, the importance of glutathione as a substantial player in the overall redox power of the parasite has been proposed [68]. Interestingly, variation in total level and the reduced: oxidized ratio of trypanothione is a typical response in antimonial treatment [69], also detected in a CE metabolomic study [56], which is in tune with partial crossresistance between these two drugs [61].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Leishmania can synthesize ascorbate as a powerful antioxidant (Manhas, Anand, Tripathi, & Madhubala, ). Therefore, we assessed the redox state of thiols in the presence of Asc, Car, and Caryo by a CMFDA assay (Sarkar et al, ) resulting in a glutathione S ‐transferase (Fyfe, Westrop, Silva, Coombs, & Hunter, ) catalyzed conjugation of MF to low molecular weight thiols. As shown, these findings are in line with superoxide radical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been indicated that thiols act as reducing agents in this conversion. Furthermore, the participation of a unique parasite-specific trimeric glutathione transferase TDR1 in the activation of antimonial prodrugs has been suggested (Fyfe et al, 2012).…”
Section: Antimonialsmentioning
confidence: 99%